Results of conservative treatment in non-advanced breast cancer.A - Leborgne, Félix; Leborgne, José H; Hekimian, Luciano; Rozada, Héctor; Ortega, Bettys; Doldan, Raquel; Osta Mendoza, Juan; Calvete, Rosario; Maisonneuve, Juan (Cirugía del Uruguay, 1989)
uthors analyse two groups of patients submitted to conservative treatment of breast cancer between 1973 and 1987.